Legal Implications of the P5 Veto Power on the Enforcement of ICJ Judgments and its Impact on the Credibility of the UN Security Council - Aidonojie, Paul Atagamen; Ismiala, Hassan Adebowale; Antai, Godswill Owoche; Ekpenisi, Collins; Obieshi , Eregbuonye (Sinergi International Journal of Law, 2026)
The formation of the United Nations and its organs is meant to steer global community affairs. Hence, the International Court of Justice (ICJ), as one of the UN organs, has been positioned to address conflicts between states. Although the enforcement of its judgment depends mainly on the UN Security Council, which has often been constrained by the P5 Veto Power. Hence, this study examines the legal implications and impact of the P5 Veto power in the enforcement of the ICJ Judgement. The study adopts a doctrinal method of study by utilising the PRISMA Guide to systematically search, evaluate and assess primary and secondary sources of research materials. Hence, several international laws and case law were relied on. Also, 48 scientific peer-reviewed secondary sources were relied on. Results indicate that enforcement outcomes are shaped less by legal obligation than by P5 political alignment, producing recurrent compliance deficits. The study therefore concludes that the P5 Veto Power generate significant legal impact and consequences in circumventing the enforcement of the ICJ Judgement. The study recommends amending the UN Charter to limit the power of the P5 in the enforcement of the ICJ Judgement. In the alternative, there should be regional cooperation in recognising and implementing the ICJ Judgement. This research is a breakthrough in the sense that it associates the P5 veto with the systematic obstruction of ICJ judgment enforcement and not with the general UN decision-making. It additionally illustrates the obstruction's impact on the Security Council's credibility in its role as the international justice custodian.